2015
DOI: 10.1039/c4ra09662b
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin facilitated electrospun chitosan nanofibers

Abstract: Cyclodextrin complexation of chitosan presents a novel route to achieve nanofibers of chitosan and other difficult-to-electrospin biopolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…The PEO polymeric matrix helps the continuous electrospinning process and higher amount of γ-CD facilitated the uniform and beadfree fiber formation mostly due to high solution viscosity. These results correlates with our previous reports [20,21] and other literature [22] where the presence of CD assist the formation of bead-free fibers from lower polymer solutions.…”
Section: Resultssupporting
confidence: 93%
“…The PEO polymeric matrix helps the continuous electrospinning process and higher amount of γ-CD facilitated the uniform and beadfree fiber formation mostly due to high solution viscosity. These results correlates with our previous reports [20,21] and other literature [22] where the presence of CD assist the formation of bead-free fibers from lower polymer solutions.…”
Section: Resultssupporting
confidence: 93%
“…The judicious choice of additive components offers a solution to offset such charge repulsion effects during electrospinning [4,7,[26][27][28][29][30]. For example, Burns et al reported the use of trifluoroacetic acid (TFA) and hydroxypropyl β-cyclodextrin (HPCD) as additives to assist in the electrospinning of chitosan nanofibers [31]. The potential of HPCD to form noncovalent host-guest complexes with various molecular species, in conjunction with the polyelectrolyte nature of chitosan, may further enhance the utility of such nanofibrous materials as advanced coating materials [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers are a unique class of materials which combine many desirable properties, including tunable mat porosity, a high surface area to volume ratio, and controlled surface functionality . These defining characteristics have generated diverse applications for nanofibers in areas ranging from filtration, energy, sensing, packaging, and biotechnology . Additionally, during nanofiber spinning, the fiber matrix can be loaded with molecules or particles to be finely tuned for a desired application.…”
Section: Introductionmentioning
confidence: 99%